Sedimentary Record of Polycyclic Aromatic Hydrocarbons in the Gulf of Trieste (Northern Adriatic Sea) - Distribution, Origin and Temporal Trends - Bajt, Oliver (Frontiers in Marine Science, 2022)
A mid-term study (2003-2013) of polycyclic aromatic hydrocarbons in Gulf of Trieste sediments was conducted at seven sampling sites. The PAH spatial and temporal distribution and origin were determined. The sediments were sampled with a gravity core sampler. After extraction of PAH, their concentrations were determined by gas chromatography. The results of the study show PAH spatial and temporal variability. The highest mean concentration was measured in the marina of Portoroz (1168 ng/g dw), and the lowest at an offshore site (320 ng/g dw). The results show higher concentrations of PAH in coastal areas and a decreasing trend towards the central part of the Gulf of Trieste. The interannual differences in the concentrations of PAH showed a significant downward trend in the marina of Portorož, in the port of Koper and in the offshore site off Piran. No trend was observed at all other sites. Various evaluation indices showed that PAH are predominantly of pyrolytic origin, with a lower proportion of petrogenic origin, especially in the Bay of Koper. The ecological risk assessment found that concentrations of PAH are well below levels associated with adverse biological effects. According to the presented results, this area can be considered as only moderately contaminated with PAH. However, the applied measures to reduce pollution should be continued and intensified.